My body is not one: body, Afro-Brazilian performing arts cultures, and curricular issues (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
Is it possible to blur the hegemony of the notion of body that governs structures of domination that imply the epistemicide of Black bodily cultures? In various cultural fields, the predominance of a conception of the body primarily oriented by biologizing criteria is observed. However, other foundations have generated notions of bodies, as well as performing arts manifestations, guided by distinct principles such as ancestry and communal life. In this study, analyses of undergraduate theater curricula, a literature review on the Black body and its foundations, and investigations into performing arts experiences that incorporated this perspective of the body in academic spaces were carried out.
Keywords: black body; afro-Brazilian performing arts cultures; curriculum